2018
DOI: 10.1186/s13568-018-0568-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of Issatchenkia orientalis under ethanol stress

Abstract: Issatchenkia orientalis, a non-Saccharomyces yeast that can resist a wide variety of environmental stresses, has potential use in winemaking and bioethanol production. Little is known about gene expression or the physiology of I. orientalis under ethanol stress. In this study, high-throughput RNA sequencing was used to investigate the transcriptome profile of I. orientalis in response to ethanol. 502 gene transcripts were differentially expressed, of which 451 were more abundant, and 51 less abundant, in cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 50 publications
(54 reference statements)
2
13
0
Order By: Relevance
“…kudriavzevii was first formally described in 1960 [ 7 ], it was reported to be able to sporulate, but cultures of the type strain were later described as being unable to conjugate or sporulate [ 8 , 9 ]. A third name, Issatchenkia orientalis , is obsolete [ 6 ] but continues to be used in the literature by some laboratories [ 10 , 11 ]. Strain CBS5147 was deposited as the type strain of I .…”
Section: Introductionmentioning
confidence: 99%
“…kudriavzevii was first formally described in 1960 [ 7 ], it was reported to be able to sporulate, but cultures of the type strain were later described as being unable to conjugate or sporulate [ 8 , 9 ]. A third name, Issatchenkia orientalis , is obsolete [ 6 ] but continues to be used in the literature by some laboratories [ 10 , 11 ]. Strain CBS5147 was deposited as the type strain of I .…”
Section: Introductionmentioning
confidence: 99%
“…During fermentation, budding yeast S. cerevisiae is responsible for the production of ethanol, while the non‐ Saccharomyces usually increase the sensory properties of wine by producing metabolites by‐products that affect aroma and structure of the wine (Minnaar et al, 2017; Morata et al, 2012). Therefore, the impact of non‐ Saccharomyces in fruit wine fermentation has become increasing attention (Ciani, Comitini, Mannazzu, & Domizio, 2010; González‐Pombo, Fariña, Carrau, Batista‐Viera, & Brena, 2011; Miao et al, 2018). Issatchenkia orientalis (synonym Pichia kudriavzevii ), belongs to nonconventional yeast, and was initially isolated from tropical fruit and food sources, which has been reported to be involved in the fermentation of several traditional African foods (Kalui, Mathara, & Kutima, 2010; Padonou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies in omics under stress conditions of budding yeast, and little researches on I. orientalis' omics has been reported (Palma et al, 2017; Zhang, Xiong, Tang, Mehmood, & Zhao, 2019). Miao et al (2018) used RNA‐Seq to study the changes in gene expression profile of I. orientalis under ethanol stress, but little is known about the cell response to the acetic acid stress condition at the transcriptional and proteomic level.…”
Section: Introductionmentioning
confidence: 99%
“…Miao et al. (2018) showed that ethanol stress could lead to the up‐regulation of HSP 90, HSP 70, and genes related to ubiquitin‐proteasome pathway, resulting in protein misfolding, and aggregation of toxic cells. In this process, the capacity of non‐Saccharomyces to produce alcohol by reducing sugar is relatively low, which is similar to the result reported by Varela et al.…”
Section: Resultsmentioning
confidence: 99%
“…As the fermentation processed, the metabolic activity of yeasts was affected by the increasing alcohol content and acidity to a certain extent, which resulted in the decreasing consumption rate of reducing sugar. The non-Saccharomyces SITCY125 achieved a cell concentration of >10 7 CFU/ml after 12 hr of fermentation, its alcoholicity of the fermentation broth reached a maximum of 4.35%vol, and the number of yeasts gradually decreased, indicating that non-Saccharomyces yeasts were sensitive to ethanol and vulnerable to the stress of ethanol Miao et al (2018). showed that ethanol stress could lead to the up-regulation of HSP 90, HSP 70, and genes related to ubiquitin-proteasome pathway, resulting in protein misfolding, and aggregation of toxic cells.…”
mentioning
confidence: 99%